Real-time visual activity feedback for physical activity improvement in breast and colon cancer patients. Issue 1 (2nd January 2017) - Gabrys, Lars; Sperzel, Stefan; Bernhoerster, Marcus; Banzer, Winfried; Vogt, Lutz
ABSTRACT: The study aims to evaluate the effects and feasibility of a biofeedback device for physical activity (PA) improvement in breast and colon cancer patients. Daily PA of 19 cancer patients was measured by accelerometry (ActiGraph, GT1 M). Additionally, patients wore a motion sensor with real-time visual activity feedback (ActiSmile). Counts per minutes (cpm) and moderate to vigorous physical activity (MVPA) were calculated and patients' activity data were compared to PA of 20 age-matched healthy controls. Baseline PA of patients was lower compared to controls. Following visual real-time feedback cancer patients increased cpm by 21% ( p = .002) and MVPA by 9% ( p = .007) compared to baseline measurement. PA levels in cancer patients obtained with visual feedback became almost equal compared to age-matched healthy controls: cpm (301; IQR 170 vs. 299; IQR 111), MVPA (36; IQR 23 vs. 41; IQR 25 min/day). Activity biofeedback seems to be feasible to induce changes in patients' PA behaviour.